2004
DOI: 10.5433/1679-0359.2004v25n4p315
|View full text |Cite
|
Sign up to set email alerts
|

Resíduos agroindustriais para produção biotecnológica de xilitol

Abstract: ResumoResíduos lignocelulósicos tais como bagaço de cana-de-açúcar, palha de arroz, casca de aveia e resíduos florestais representam fontes abundantes e não dispendiosas de carboidratos (celulose e hemicelulose) com potencial aplicação em processos de conversão química ou microbiana em produtos de interesse comercial. Xilose, o açúcar predominante na fração hemicelulósica pode ser convertido em xilitol. O xilitol é um poliol com propriedades físico-química importantes para as indústrias alimentícia e farmacêut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
2
3
0
6
Order By: Relevance
“…These results are consistent with others reported in the literature, which the authors report that the corn strover contains about 41.2 % cellulose, about 34.5 % of hemicellulose and 8.7 % lignin [13].…”
Section: Composition Of Corn Stover Fibersupporting
confidence: 93%
“…These results are consistent with others reported in the literature, which the authors report that the corn strover contains about 41.2 % cellulose, about 34.5 % of hemicellulose and 8.7 % lignin [13].…”
Section: Composition Of Corn Stover Fibersupporting
confidence: 93%
“…For the concentrations of acetic acid (19.00 mg/L), HMF (0.09 mg/L) and furfural (0.06 mg/L) after detoxification process, it is observed that the behavior was coherent to the reported by Felipe (2006), Carvalho et al (2005) and Tamanini and Hauly (2004). It has been found that the process of detoxification promoted partial removal of acetic acid, HMF and furfural, respectively.…”
Section: Resultssupporting
confidence: 79%
“…Waste production in these segments can reach about 250 million tons per year [6]. Particleboard (or MDP) can be produced from any lignocellulosic material which provides high mechanical strength and specific weight according to standards, just because lignocellulosic structure is similar to timber [7].…”
Section: Introductionmentioning
confidence: 99%